2015
DOI: 10.1590/1413-78522015230300816
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of falls in elderly women

Abstract: OBJECTIVE: To verify prevalence of falls and fear of falling, and to compare functional fitness among elderly women fallers and non-fallers. METHODS: Seventy-eight elderly women participated in this study. Cases of falls and the fear of falling were self-reported by the elderly women, while the functional fitness was measured by a set of functional tests. Mean and standard deviation were used to describe the sample. Independent t-test was used to compare functional fitness between groups. RESULTS: The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(41 reference statements)
1
4
0
4
Order By: Relevance
“…Age is one of the key risk factors for falls and the risk of falling increases with age [13]. Another study, which included a large sample of elderly persons, found that probability of falling increased with age [14]. According to some studies that investigated the relationship between falls and risk factors associated with falling, age was in a statistically significant correlation with falling [15].…”
Section: Discussionmentioning
confidence: 99%
“…Age is one of the key risk factors for falls and the risk of falling increases with age [13]. Another study, which included a large sample of elderly persons, found that probability of falling increased with age [14]. According to some studies that investigated the relationship between falls and risk factors associated with falling, age was in a statistically significant correlation with falling [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ao se exporem mais, aumenta-se o risco de traumas de maior impacto, ao ar livre, como atropelamentos e queda de escadas. Além disso, podemos perceber que no grupo >80 anos há uma maior prevalência de traumas de fêmur, possivelmente explicados por uma maior pela alta prevalência de quedas de próprio nível e da cama, bem como fatores de risco como osteoporose, sobretudo em uma população com mais mulheres, observados em estudos publicados no Brasil 3,6 . Isso reforça não só a importância de medidas preventivas direcionadas, como levanta também tópicos importantes a serem considerados pelos serviços de saúde que prestam assistência a esses pacientes, como medidas para facilitar diagnóstico precoce e tratamento adequado das repercussões clínicas que as quedas nos diferentes grupos podem ter, haja vista as diferentes complicações e prognósticos dos tipos de fratura identificados.…”
Section: Discussionunclassified
“…No presente estudo encontramos menor preocupação com a ocorrência de quedas e melhor equilíbrio e marcha nas pacientes ativas em relação às idosas sedentárias. Estudos realizados com propósito de verificar a funcionalidade de mulheres na terceira idade que sofrem ou não quedas e sentem ou não preocupação com a possibilidade de cair, são interessantes por conceder a possibilidade de traçar o perfil desta população, e com isso produzir informações que colaboram com os fisioterapeutas e equipe interdisciplinar, na criação de estratégias para prevenir quedas e suas consequências na capacidade funcional dos acometidos 11,12 .…”
Section: Discussionunclassified
“…A preocupação com a possibilidade de cair é um problema influenciado por diversos fatores, sejam eles ambientais, psicológicos ou físicos. Um estudo realizado em 2015 mostrou evidências de que idosas que sofrem quedas tem menor aptidão funcional, principalmente em relação à agilidade, força muscular e equilíbrio 12 . Em contra partida, a prática de exercício físico é capaz de contribuir para melhora da capacidade funcional, equilíbrio, agilidade e coordenação, qualidade de vida e força muscular, bem como reduzir fatores de risco que podem levar a quedas 13,14 .…”
Section: Discussionunclassified
See 1 more Smart Citation